Patience Therapy to Reduce Adolescents' Anxiety Assessed from Personality and Parenting - Risydah Fadilah; Abd. Madjid (International Journal of Islamic Educational Psychology, 2020)
The character or personality possessed by students is inseparable from the parenting process at home and the influence of the social environment. The research method used was Quasi-Experimental. The results of data processing obtained results for anxiety, namely for the experimental group, the value of Z = -1,362ª with p = 0,173 since p 0.173 0.05. This result means that there was a decrease in anxiety symptoms that were not so significant after being given a pretest and posttest in the experimental group. For the control group, the value of Z = -0.440ª was with p = 0.660 since p 0.660 0.05. This result means that there was a decrease in anxiety symptoms that were not so significant before (pretest) and after (posttest) in the control group. The results of data processing obtained results for patience, that was for the experimental group, the value of Z = -2.666ª with p = 0.008 since p 0.008 0.05, then H0 was rejected, and H1 was accepted. This result means that there was a significant increase in patience after a pretest and posttest in the experimental group. For the control group, the value of Z = -1.629ª was with p = 0.103 since p 0.103 0.05, H0 was accepted, and H1 was rejected. This result means that there was no significant increase in patience before (pretest) and after (posttest) in the control group.